2015
DOI: 10.1016/j.mce.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reactivation of p21CIP1/WAF1 and KLOTHO by a combination of bioactive dietary supplements is partially ERα-dependent in ERα-negative human breast cancer cells

Abstract: Available treatment strategies against estrogen receptor (ER)-negative breast cancer patients are limited due to their poor response to hormonal therapy. We have shown previously that the combinations of green tea polyphenols (GTPs), a dietary DNA methyltransferase inhibitor, and sulforaphane (SFN), a dietary histone deacetylase inhibitor, reactivate ERα expression in ERα-negative MDA-MB-231 cells. Here, we investigated the functional significance of ERα reactivation in the reactivation of silenced tumor suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…The CDKN1A encodes p21 CIP1/WAF1 protein, a cyclin‐dependent kinase inhibitor (CDKI), which acts as a tumor suppressor and induces G1 or G2/M cell cycle accumulation, proliferation inhibition, and apoptosis . Expression of p21 CIP1/WAF1 may epigenetically be inactivated in different cancers including breast cancer . In the current study, we demonstrated that application of miR‐302/367 together with miR‐16 can induce upregulation of CDKN1A expression in breast cancer cells.…”
Section: Discussionmentioning
confidence: 66%
“…The CDKN1A encodes p21 CIP1/WAF1 protein, a cyclin‐dependent kinase inhibitor (CDKI), which acts as a tumor suppressor and induces G1 or G2/M cell cycle accumulation, proliferation inhibition, and apoptosis . Expression of p21 CIP1/WAF1 may epigenetically be inactivated in different cancers including breast cancer . In the current study, we demonstrated that application of miR‐302/367 together with miR‐16 can induce upregulation of CDKN1A expression in breast cancer cells.…”
Section: Discussionmentioning
confidence: 66%
“…SFN treatment inhibits the cell proliferation through decreased expression level of Bmi‐1 and Ezh2. In one of our recent finding, we demonstrated that the combinations of green tea polyphenols (GTPs), a dietary DNMTs inhibitor with SFN, reactivate key tumor suppressor genes such as p16 , p21, and Klotho through active chromatin modifications . SFN not only reactivates tumor suppressor genes but also silences the key tumor promoter gene through epigenetic regulations .…”
Section: Sulforaphanementioning
confidence: 99%
“…Genistein 38 is an isoflavone naturally contained in soybean, able to inhibit DNMT and HDAC enzymes and showing anticancer properties in cells . Recently, genistein 38 has been reported to: (i) arrest breast cancer cells cycle in G 2 /M phase inducing the expression of p21 WAF1/CIP1 ; (ii) resensitize estrogen receptor (ER)‐negative breast cancer cells to estrogen‐targeted chemotherapy through the activation of ER; (iii) increase the acetyl‐H3 and acetyl‐H4 levels as well as dimethyl‐ and trimethyl‐H3K4 at the promoter region of the BTG3 gene in renal cancer; (iv) increase the acetylation status of H3K4 at the p21 WAF1/CIP1 and p16 INK4a transcription start sites, mediated by induction of HATs in prostate cancer …”
Section: The Mmt Approachmentioning
confidence: 99%